The Political Economy of Integration in the European Community / Second Edition - Edward Elgar; Harrop Jeffrey (1992)
This book provides detailed coverage of the key areas of economic activity. Preface, Abbreviations, Introduction, Organizational Stepping Stones, The Structure and Operation of Community Institutions, Free Trade and the Customs Union and Internal Market, Agriculture and Fisheries, Industrial and Technological Policies, Regional and Social Problems and Policies, Monetary Integration, Fiscal Policy: Taxation and the Community Budget, World-Wide Trading Links, Enlargement and Integration: Prospect and Retrospect, Bibliography, Index.